Consumerism as a Substitute for the Quality of Life - Słaby, Teresa (Konsumpcjonizm substytutem jakości życia, 2009)
For the last few years, the quality of life of Polish citizens (Poles) depends to a great extent on the possessed, often entirely unnecessary, goods. The quality of life nowadays results more from the supremacy of pleasant feelings coming from excessive consumption rather than the positive evaluation of life as a whole. The paper presents results of qualitative research in Warsaw and Lublin (2007). The research’s main objectives were answers to the questions: does consumerism still strongly characterize the consumers’ behaviours; does excessive purchasing of goods create a sense of happiness; do the regional diversities exist and could some symptoms of the restrictions of such behaviours be observed? The findings have not been consoling in this context.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 73, s. 98-104